Ensuring road safety at regulated intersections in the presence of turning flows - O. S. Gasilova; M. V. Gryaznov; O. A. Pytaleva (Интеллект. Инновации. Инвестиции)
This study is the result of collaboration between specialists of the Ural State Forest Engineering University and the Nosov Magnitogorsk State Technical University. Having compared the results of their own independently conducted studies, the authors came to the conclusion that ensuring road safety at controlled intersections in medium and large cities has a common scientific and methodological basis. Existing methods for calculating the duration of traffic light control cycles are aimed at ensuring maximum throughput in all directions of traffic at the intersection. Experts also assume that the main thing in determining the duration of the traffic light control cycle is to ensure road safety. However, in modern scientific literature there are few works devoted to modeling the movement of vehicles with the condition of accident-free passage through the intersection.